Digital interventions to moderate alcohol consumption in young people: a Cancer Prevention Europe overview of systematic reviews - McDermott, Kevin T.; Noake, Caro; Wolff, Robert; Espina, Carolina; Foucaud, Jérôme; Steindorf, Karen; Schüz, Joachim; Thorat, Mangesh A.; Weijenberg, Matty; Bauld, Linda; Kleijnen, Jos (Frontiers in Digital Health, 2023)
Background The increasing accessibility and applicability of digital technologies make these powerful tools to facilitate behavioural changes in young people (<25 years) which could translate into public health improvements. Objective To ascertain (1) are digital interventions aimed at young people effective in addressing alcohol consumption? and (2) What is the quality and strength of the systematic review evidence? Methods Searches were conducted across relevant databases including KSR Evidence, Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE). Records were independently screened. Risk of bias (RoB) was assessed with the ROBIS checklist. We employed a narrative analysis. Results Twenty-seven systematic reviews were included but those reviews were mostly assessed as low quality. Definitions of ‘digital intervention’ greatly varied and overlapped. Evidence was limited by sub-population and intervention type. For the purposes of this abstract we have included only selected results. See article for full details. The use of computer or mobile device-based interventions resulted in reduced alcohol consumption when comparing with no/minimal intervention (-13.4 g/week, 95% CI -19.3 to -7.6, review rated low RoB, moderate to substantial heterogeneity). While in risky drinkers aged 15 to 25, Computerized interventions reduced short (SMD: - 0.17, 95% CI: -0.27 to -0.08) and long term (SMD: -0.17, 95% CI: -0.30 to -0.04) alcohol consumption compared to no intervention, while a small effect (SMD: -0.15, 95% CI: -0.25 to -0.06) in favour of computerised assessment and feedback versus assessment only was observed. However, no short-term (SMD: -0.10, 95% CI: -0.30 to 0.11) or long-term effect (SMD: -0.11, 95% CI: -0.53 to 0.32) was demonstrated for computerised brief interventions when compared to counsellor-based interventions (review rated low RoB, minimal to considerable heterogeneity). For all results, interpretation has limitations in terms of risk of bias and heterogeneity. Conclusion Limited evidence suggests some potential for certain digital interventions in sub-populations of younger people. However, this effect is often small and inconsistent. Systematic review evidence is generally low quality. Further research is warranted to explore the full potential of digital interventions and to form the basis of evidence based public health initiatives.